Genome-wide identification, evolutionary selection, and genetic variation of DNA methylation-related genes in Brassica rapa and Brassica oleracea - Feng AN; Kang ZHANG; Ling-kui ZHANG; Xing LI; Shu-min CHEN; Hua-sen WANG; Feng CHENG (Journal of Integrative Agriculture, 2022)
DNA methylation plays an important role in plant growth and development, and in regulating the activity of transposable elements (TEs). Research on DNA methylation-related (DMR) genes has been reported in Arabidopsis, but little research on DMR genes has been reported in Brassica rapa and Brassica oleracea, the genomes of which exhibit significant differences in TE content. In this study, we identified 78 and 77 DMR genes in Brassica rapa and Brassica oleracea, respectively. Detailed analysis revealed that the numbers of DMR genes in different DMR pathways varied in B. rapa and B. oleracea. The evolutionary selection pressure of DMR genes in B. rapa and B. oleracea was compared, and the DMR genes showed differential evolution between these two species. The nucleotide diversity (π) and selective sweep (Tajima’s D) revealed footprints of selection in the B. rapa and B. oleracea populations. Transcriptome analysis showed that most DMR genes exhibited similar expression characteristics in B. rapa and B. oleracea. This study dissects the evolutionary differences and genetic variations of the DMR genes in B. rapa and B. oleracea, and will provide valuable resources for future research on the divergent evolution of DNA methylation between B. rapa and B. oleracea.